THE MAIN TRENDS OF INTERACTION BETWEEN THE ADMINISTRATION OF ROSPOTREBNADZOR IN THE LENINGRAD REGION AND THE GOVERNMENT OF LENINGRAD REGION IN THE FIELD OF POPULATION RADIATION PROTECTION - S. A. Gorbanev; L. A. Eremina; N. N. Kurganov (Радиационная гигиена)
The article gives the main interaction trends of the Administration of Rospotrebnadzor in the Leningrad Region and the Government of Leningrad Region regarding issues of regional radiation protection. It reports on comprehensive measures devoted to the limitation of the population exposure from natural irradiation sources, monitoring of territories which suffered from Chernobyl NPP accident and monitoring of the environmental impact of unauthorized dumps and solid municipal waste sites in the Leningrad Region. It presents the basic issues of medical exposure limitation in the Leningrad Region and measures for their solving.